Pengaruh Self-Compassion terhadap Tingkat Flourishing pada Tenaga Kesehatan di Indoenesia - Yolina Njotowibowo; Agustina Engry (Personifikasi: Jurnal Ilmu Psikologi, 2023)
Flourishing is an individual’s condition that shows optimal self-development and is able to carry out its functions properly based on their strengths. One of the factors that determines the levels of flourishing is self-compassion. Self-compassion is defined as a form of behavior that opens and accepts one’s feelings when someone experiences difficult situations. The purpose of this study was to determine the effect of self-compassion on flourishing among healthcare workers in Indonesia.The sampling technique used in this study was purposive sampling. The measures used were the flourishing scale which is based on 5 aspects, namely positive emotion, engagement, relationship, meaning, and achievement, and the self-compassion scale which is based on 3 components, namely self-kindness vs self-judgement, common humanity vs isolation, mindfulness vs over-identification. In this study, the respondents were 122 subjects. Data analysis was carried out using simple regression analysis with the help of the SPSS for windows 23.0. The resul revealed F = 41,508 and p = 0,000 (p